2016
DOI: 10.18593/eba.v16i1.9996
|View full text |Cite
|
Sign up to set email alerts
|

FREE CULTURE MEDIA OF GROWTH REGULATORS ON MICROPROPAGATION OF GRAPEVINE (Vitis labrusca L.) ‘BORDÔ’ CULTIVAR THROUGH NODAL SEGMENTS

Abstract: The micropropagation is an important biotechnological tool for obtaining and maintaining mother grapevine plants with high quality plant health. The objective was to evaluate the establishment and multiplication in vitro and ex vitro acclimatization of grapevine cultivate Bordô in different culture media without adding growth regulators. Grapevine nodal segments were cultured in five culture media formulations without adding growth regulators. It was evaluated the number of leaves and roots, length of roots an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The effectiveness of a propagation protocol depends largely on the rate of shoot multiplication [ 52 ]. The shoot multiplication rate (MR) reflects the number of new progeny plants produced from a single explant [ 56 , 72 ]. We found that the concentration of phytohormones and the acidity of the culture medium have a great effect on the MR and the quality of in vitro stock cultures ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of a propagation protocol depends largely on the rate of shoot multiplication [ 52 ]. The shoot multiplication rate (MR) reflects the number of new progeny plants produced from a single explant [ 56 , 72 ]. We found that the concentration of phytohormones and the acidity of the culture medium have a great effect on the MR and the quality of in vitro stock cultures ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%